Does tourism increase energy consumption in BRICS countries? - Visas, Hubert; Rehan, Raja; Ul-Haq, Jabbar; Cheema, Ahmed Raza; Khanum, Sana; Hye, Qazi Muhammad Adnan (Journal of Tourism Management Research, 2023)
Tourism has been the fastest-growing sector in the world over the last decade, contributes to employment opportunities, and generates earnings in foreign currencies. Tourism intensively needs energy to promote tourist activities, which in turn causes economic growth. However, as almost all tourist activities, like hotel accommodations and transportation, strongly depend on energy use, it may contribute to increased energy consumption. Our study explores the impact of tourism on energy consumption in the BRICS (i.e., Brazil, Russia, India, China, and South Africa) by using the panel data set of 1995–2014. In this study, feasible generalized least squares (FGLS) and Panel corrected standard error (PCSE) panel regression techniques are used for empirical analysis. The results reveal that tourism has a positive and significant impact on energy consumption. Our findings are robust and unaffected by the use of various energy consumption proxies and econometric techniques. Furthermore, our findings are robust and significant due to the inclusion of various controls such as financial development, gross fixed capital formation, total population, and gross domestic product. The policy implication is that governments should promote the tourism sector as a way to boost the growth of their economies. Sustainable tourism can help these economies achieve sustainable development.